Level of job satisfaction and level of organizational citizenship behavior among lecturers of the Islamic University of Melaka College - Puteh, Baharuddin; Omar Mokhtar, Muhammad Yasin; Ibrahim, Ahmad Zulfandi; Wan Othman, Wan Norhayati; Sheikh Kamaruzaman, Syarifah Syarina (Human Resource Management Academic Research Society, 2021)
In the daily work of lecturers, they are bound to face several aspects such as students, documentations and KUIM, having the status of a private University Colleges they also have to deal with the admission of students which is one of their annual KPIs. This will definitely affect the lecturers both in the short and long term. Therefore, the behavior that needs to be demanded and possessed such as Organizational Citizenship Behavior (TKO) is actually able to create a good work ethic for an employee. As such, this study focuses on the findings that look into the TKO level and job satisfaction of KUIM lecturers. The results showed a high level of TKO but the level of work satisfaction was moderate. These findings could be further extended into details for there are more researchers that could be taken into account. These findings could be utilized by the Human Resources department for planning and developing suitable trainings and courses.